There's a girl in my hammerlock - Spinelli, Jerry (New York : Simon & Schuster, 1991)
Thirteen-year-old Maisie joins her school's formerly all-male wrestling team and tries to last through the season, despite opposition from other students, her best friend, and her own teammates.
Children's Catalog (Wilson)
Junior High School Library Catalog (Wilson)
Publishers Weekly Editors' Choice
5.5
5-8
Keywords: Schools -- Fiction; Wrestling -- Fiction; Sex role -- Fiction; School stories